2007
DOI: 10.1016/j.ppnp.2006.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Chiral perturbation theory beyond one loop

Abstract: The existing Chiral Perturbation Theory (ChPT) calculations at order p 6 are reviewed. The principles of ChPT and how they are used are introduced. The main part is a review of the twoand three-flavour full two-loop calculations and their comparison with experiment. We restrict the discussion to the mesonic purely strong and semileptonic sector. The review concludes by mentioning the existing results in finite volume, finite temperature and partially quenched ChPT. Chiral Perturbation Theory Beyond One Loop A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 223 publications
(499 reference statements)
2
107
0
Order By: Relevance
“…Calculations up to NNLO are clearly useful to settle the issue [10][11][12][13]. An exploratory study of the RBC/UKQCD data [4,5] on K ℓ3 form factors and F K /F π (the ratio of the kaon and pion decay constants) showed that NNLO terms are not negligible though of the expected size, the NLO terms of some observables being in this particular study anomalously small for some known reasons.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Calculations up to NNLO are clearly useful to settle the issue [10][11][12][13]. An exploratory study of the RBC/UKQCD data [4,5] on K ℓ3 form factors and F K /F π (the ratio of the kaon and pion decay constants) showed that NNLO terms are not negligible though of the expected size, the NLO terms of some observables being in this particular study anomalously small for some known reasons.…”
Section: Introductionmentioning
confidence: 70%
“…The third quantity measures the relative size of the quark masses in a framework where the strange quark is supposed to play a peculiar role in the chiral structure of QCD vacuum. In the following, we will also use the quantity Y (3): 10) which assesses the saturation of the chiral expansion of the pion mass by its leading order.…”
Section: Jhep01(2011)107mentioning
confidence: 99%
See 1 more Smart Citation
“…An introduction to ChPT can be found in [23,24] and in the two-loop review [25]. The lowest order and p 4 -Lagrangian can be found in [4].…”
Section: Jhep11(2015)097 2 Partially Quenched Chiral Perturbation Theorymentioning
confidence: 99%
“…This input is especially welcome for LECs modulating quark mass terms: unlike in phenomenological analyses, quark (and hadron) masses can be tuned on the lattice. a e-mail: Gerhard.Ecker@univie.ac.at b e-mail: masjuan@kph.uni-mainz.de c e-mail: helmut.neufeld@univie.ac.at While this program has been very successful for chiral SU (2), the situation is less satisfactory for SU (3) [1]. In the latter case, the natural expansion parameter (in the meson sector) is M 2 K /16π 2 F 2 π 0.2.…”
Section: Introductionmentioning
confidence: 99%